Exogenous Uniconazole promotes physiological metabolism and grain yield of rice under salt stress - Du, Xiaole; Du, Youwei; Feng, Naijie; Zheng, Dianfeng; Zhou, Hang; Huo, Jingxin (Frontiers in Plant Science, 2024)
Salt stress severely inhibit plant growth and development. Uniconazole has been considered to significantly increase plant stress tolerance. However, the mechanism by which Uniconazole induces salt tolerance in rice seedlings and its impact on yield is still unclear. In this study, the effects of exogenous Uniconazole on morphogenesis, physiological metabolism, and yield of rice seedlings under salt stress were analyzed using the salt-tolerant rice variety HD961 and the salt-sensitive rice variety 9311. The results showed that salt stress significantly inhibited rice growth, disrupted the antioxidant system and pigment accumulation, and reduced photosynthesis, and yield. There were corresponding percent decreases of 13.0% and 24.1% in plant height, 31.6% and 55.8% in leaf area, 65.7% and 85.3% in root volume, respectively for HD961 and 9311. spraying However, compared to salt stress, the US treatment increased the percentage to 4.7% and 139.0% in root volume, 7.5% and 38.0% in total chlorophyll, 4.5% and 14.3% in peroxidase (POD) of leaves, 14.4% and 54.2% in POD of roots, 18.7% and 22.7% in catalase (CAT) of leaves, and 22.6% and 53.9% in CAT of roots, respectively, for HD961 and 9311. In addition, it also significantly enhanced photosynthesis at the reproductive stage, promoted the transport of carbohydrate to grains. And US treatment significantly increased the percentage to 9.0% in panicle length, 28.0% in panicle number per hole, 24.0% in filled grain number, 3.0% in 1000-grain weight, and 26.0% in yield per plant, respectively, for HD961, compared to salt stress. In summary, applying Uniconazole at the seedling stage can alleviate the damage induced by NaCl stress on rice by regulating the physiological metabolism of rice plants. This reduces the negative effects of salt stress, enhance salt tolerance, and boost rice production.